1998
DOI: 10.1200/jco.1998.16.11.3584
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of transcription factor AP-2 predicts poor survival in stage I cutaneous malignant melanoma.

Abstract: The loss of AP-2 expression seems to be associated with malignant transformation and tumor progression in cutaneous malignant melanoma. This tumor-suppressive action of AP-2 may be mediated through p21 regulation. Furthermore, decreased AP-2 expression is independently associated with elevated risk of subsequent metastatic behavior of stage I cutaneous malignant melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
89
3

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 29 publications
15
89
3
Order By: Relevance
“…Immunohistochemical studies have shown that downregulated cytoplasmic AP-2a expression was consistently seen in high grade and advanced Duke's stage tumors (Ropponen et al, 2001). In addition, low cytoplasmic AP-2a expression was seen in high-grade carcinomas (Ropponen et al, 2001), corroborating previous reports in which low AP-2a expression was associated with higher tumor malignancy and poor survival (Karjalainen et al, 1998;Ropponen et al, 1999;Pellikainen et al, 2003). However, the exact mechanism by which loss of AP-2a contributes to colon cancer progression is yet to be investigated.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Immunohistochemical studies have shown that downregulated cytoplasmic AP-2a expression was consistently seen in high grade and advanced Duke's stage tumors (Ropponen et al, 2001). In addition, low cytoplasmic AP-2a expression was seen in high-grade carcinomas (Ropponen et al, 2001), corroborating previous reports in which low AP-2a expression was associated with higher tumor malignancy and poor survival (Karjalainen et al, 1998;Ropponen et al, 1999;Pellikainen et al, 2003). However, the exact mechanism by which loss of AP-2a contributes to colon cancer progression is yet to be investigated.…”
Section: Introductionsupporting
confidence: 87%
“…Loss of AP-2a expression has been associated with progression of melanoma , prostate cancer (Ruiz et al, 2004) and colorectal cancer (Ropponen et al, 1999(Ropponen et al, , 2001). In addition, immunohistochemical studies of human melanoma, breast and colorectal cancer specimens have revealed that loss of AP-2a coincides with poor prognosis (Karjalainen et al, 1998;Ropponen et al, 1999;Pellikainen et al, 2004). We have demonstrated previously that normal melanocytes and nonmetastatic melanoma cell lines express high levels of AP-2a.…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, it has been reported that overexpression of AP-2 in highly metastatic melanoma cell lines inhibits their tumor growth and metastatic potential in nude mice ). Finally, a significant negative correlation between AP-2 expression level and elevated risk of subsequent metastatic behavior has been described (Huang et al, 1998;Karjalainen et al, 1998;Baldi et al, 2001a).…”
Section: Genetics Of Cutaneous Melanomamentioning
confidence: 96%
“…Moreover, the loss of AP-2 expression seems to be associated with malignant transformation and tumor progression in malignant melanoma Gee et al, 2000;Bar-Eli, 2001;Tellez et al, 2003). Decreased AP-2 expression is associated with elevated risk of subsequent metastatic behavior in stage I cutaneous malignant melanoma (Karjalainen et al, 1998;Karjalainen et al, 2000). Re-expression of AP-2 in the highly metastatic melanoma cells decreased their tumorigenicity and inhibited their metastatic potential in nude mice (Bar-Eli, 2001).…”
Section: Introductionmentioning
confidence: 99%